Implementasi Psikologi Manajemen di Lembaga Pendidikan: Analisis Lingkungan Kerja, Motivasi, dan Kinerja Pendidik - Azizatun Nisa; Nadiyatul Kholifah; Nirmala Sari; Mualimin Mualimin (Jurnal Manajemen Bisnis Digital Terkini, 2026)
Management psychology is an important approach in managing educational organizations, as it emphasizes understanding individual behavior, motivation, and patterns of interaction within an institution. In practice, educational management requires not only managerial skills but also insight into psychological factors that influence teachers’ performance, the learning process, and overall organizational dynamics. Therefore, studying management psychology is relevant to examine how these concepts are applied in educational settings. This study aims to explore the development of research on management psychology in the field of education and to identify its role and contribution to improving the effectiveness of educational organizations. The research questions addressed in this study are: (1) how has management psychology been developed in educational research, and (2) how does it contribute to enhancing the effectiveness of organizational management in education? This research employs a qualitative literature review method. The literature search was conducted using the Google Scholar database with the assistance of the Publish or Perish application, using the keyword “management psychology.” From the initial 30 articles identified, a screening and selection process was carried out, resulting in 5 articles that were analyzed in depth. The findings reveal three main themes in the literature: classroom and learning management, leadership in educational organizations, and the development of work environment and human resource performance. These results indicate that management psychology plays a significant role in improving the effectiveness of educational institutions. Therefore, future research is recommended to examine the empirical application of management psychology across various educational organizational contexts in order to gain a more comprehensive understanding.